Uncover valuable information and solutions with IDNLearn.com's extensive Q&A platform. Ask any question and receive accurate, in-depth responses from our dedicated team of experts.
Sagot :
To solve the given system of equations, we need to find the point [tex]\((x, y)\)[/tex] that satisfies both equations simultaneously. The given equations are:
[tex]\[ \begin{array}{l} y = -3x + 6 \\ y = 2x - 4 \end{array} \][/tex]
To find the solution, follow these steps:
1. Set the equations equal to each other because both expressions on the right-hand side are equal to [tex]\(y\)[/tex]. Therefore, we can write:
[tex]\[ -3x + 6 = 2x - 4 \][/tex]
2. Combine like terms to isolate [tex]\(x\)[/tex]. Move all [tex]\(x\)[/tex]-terms to one side of the equation and the constant terms to the other side:
[tex]\[ -3x + 6 = 2x - 4 \][/tex]
First, we subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ -3x - 2x + 6 = -4 \][/tex]
[tex]\[ -5x + 6 = -4 \][/tex]
Next, we subtract 6 from both sides:
[tex]\[ -5x = -4 - 6 \][/tex]
[tex]\[ -5x = -10 \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides of the equation by [tex]\(-5\)[/tex]:
[tex]\[ x = \frac{-10}{-5} \][/tex]
[tex]\[ x = 2 \][/tex]
4. Substitute [tex]\(x\)[/tex] back into one of the original equations to find the value of [tex]\(y\)[/tex]. We'll use the first equation [tex]\(y = -3x + 6\)[/tex]:
[tex]\[ y = -3(2) + 6 \][/tex]
[tex]\[ y = -6 + 6 \][/tex]
[tex]\[ y = 0 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{(2, 0)} \][/tex]
[tex]\[ \begin{array}{l} y = -3x + 6 \\ y = 2x - 4 \end{array} \][/tex]
To find the solution, follow these steps:
1. Set the equations equal to each other because both expressions on the right-hand side are equal to [tex]\(y\)[/tex]. Therefore, we can write:
[tex]\[ -3x + 6 = 2x - 4 \][/tex]
2. Combine like terms to isolate [tex]\(x\)[/tex]. Move all [tex]\(x\)[/tex]-terms to one side of the equation and the constant terms to the other side:
[tex]\[ -3x + 6 = 2x - 4 \][/tex]
First, we subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ -3x - 2x + 6 = -4 \][/tex]
[tex]\[ -5x + 6 = -4 \][/tex]
Next, we subtract 6 from both sides:
[tex]\[ -5x = -4 - 6 \][/tex]
[tex]\[ -5x = -10 \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides of the equation by [tex]\(-5\)[/tex]:
[tex]\[ x = \frac{-10}{-5} \][/tex]
[tex]\[ x = 2 \][/tex]
4. Substitute [tex]\(x\)[/tex] back into one of the original equations to find the value of [tex]\(y\)[/tex]. We'll use the first equation [tex]\(y = -3x + 6\)[/tex]:
[tex]\[ y = -3(2) + 6 \][/tex]
[tex]\[ y = -6 + 6 \][/tex]
[tex]\[ y = 0 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{(2, 0)} \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the answers you need. Thank you for visiting, and we look forward to helping you again soon.